Qualitative and quantitative evaluation of the ventricular system and brain parenchyma in healthy dogs of different skull conformation on computed tomography scans - Doiche, Danuta Pulz [UNESP]; Rahal, Sheila Canevese [UNESP]; Silva, Jeana Pereira da [UNESP]; Oliveira, Flávia Augusta [UNESP]; Miqueleto, Nélida Simone Martinez Landeira [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Vulcano, Luiz Carlos [UNESP] (Wiley, 2022)
This study aimed to perform quantitative and qualitative evaluations of the lateral and third ventricles, and brain parenchyma, in healthy dogs of different skull conformations on CT scans. Forty-five adult client-owned dogs were divided into three groups according to skull conformation: G1 (dolichocephalic)—15 German Shepherds; G2 (mesaticephalic)—15 Rottweilers; G3 (brachycephalic)—15 Boxers. Transverse plane images were used for quantitative and qualitative evaluations of the lateral ventricles and third ventricle, and pre- and post-contrast brain parenchyma. The height of both ventricles and brain was measured at the level of the interthalamic adhesion. Ventricle height, brain height, and ventricle/brain height ratio were statistically higher in G3 compared with G1 and G2 that were similar. The third ventricle was visible but unmeasurable in five dogs from G1 and three from G2. In G3, all dogs had third ventricle visible and measurable in all images. Asymmetric ventricles were seen in five dogs in Group 1 and Group 2, and seven in Group 3. Brain parenchyma had homogenous density in 80% of the dogs in all groups. Contrast enhancement of the rostral midline was visualized in all dogs. In conclusion, brain CT scans of healthy dogs showed that the qualitative data were similar among groups, but lateral ventricle and brain measurements in brachycephalic dogs differed from the dolichocephalic and mesaticephalic dogs.